Decrease of Fuel Consumption and Emission of 4 Stroke Otto Engine due to Ground Strap Installation - Dantes, Kadek Rihendra; Dharmawan, I Made jati; Wiratmaja, I Gede (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
This study is to determine fuel consumption and exhaust emissions due to addition of a ground strap to the spark plug coil cable using silver wire material. The silver wire was 0.8 mmdiameter and installed with number of turns of 255. This research was conducted since spark plug disturbance, due to electromagnetic field, decreases engine performance. This electromagnetic field occurs during electric current flows from battery to spark plug. This study applied experimental method with 10 repetitions of data collection. The results showed that the lowest specific fuel consumption reduction by 19.6% occured at 5000 rpm and the highest one by 29% occured at 8000 rpm when groundstrap was installed. Meanwhile, HC, CO and CO2 exhaust emissions decreased by 80.3%, 82.3% and 36.7%, repectively, after installation of groundstrap.